Hearing their voices : building a career development model for women in engineering - Newhouse-Maiden, Lesley Patricia (Curtin University, 2002)
This study is an interpretive investigation of the life-career histories of 53 women in engineering; and a case study of one woman's account of present-lived career and her quest for identity in engineering over an eight year period (1992-1999). This study had two broad aims. First, it aimed to give voice to women's stories derived from their own reflective accounts, and to compare and contrast their perspectives with feminist writers' reviews of non-traditional girls' and women's career experiences, and with the organisational career story of itself. Second, it aimed to evaluate the adequacy of my convergence of a socialist feminist "unified systems" theory of social relations (Jaggar, 1983, 1989; Jaggar & Rothenberg, 1984, 1993) with Super's segmental life-span, lifespace theory (Super, 1980, 1990, 1994) to explain women's career and personality development. Further to this theoretical convergence, I elaborated on Super's original models and evaluated their usefulness for my gender analysis of career from four perspectives. I conceptualised "career" as both "subjective" and "organisational" (Dale, 1972; Hughes, 1937) and, using Benhabib's (1986b) terminology, created four perspectives by further differentiating career into either "generalised other" or "concrete other" (see Figure 1.1). Drawing on the findings of my exploration of the women's careers, I extended the range of Jaggar's/Super's explanatory theories of career and personality development (Figure 2.2) in an elaboration of Supers archway model (Figure 8.1). I found that my combined Jaggar/Super career archway and spider web model (Figure 2.3) represented the life-space tensions in each individual woman's career decision-making in engineering.The life-career rainbow was a valuable subsidiary model (Figure 2.4) in highlighting the complexities of gender as an overarching socio-cultural factor for theoretical and conceptual analyses of career and its effect on salient role relationships and personality development at each life-stage. My convergence career ladder represented the organisational career statuses and the successive development of the subjective career and identity through the completion of developmental tasks (Figure 2.6). My case study Cecilia, in common with other participants, I found to be an accomplished "feminine ambivalent" (Douvan & Adelson, 1966) and "paver of the way" (Josselson, 1987), yet she (like several others) floundered in the milieux of engineering. Her story indicates the continued need for engineering educators: to acknowledge the significance of women's subjective constructs of career to effect transformative change by promoting equity and excellence; to recognise ways in which the subjective and the organisational constructs of career can complement one another; and to implement changes which facilitate such complementarity. This study fills a space in the research literature on non-traditional girls' and women's career development. It also has potential to assist those who wish to gain a better understanding of the career pathways of women in engineering.